2018
DOI: 10.7554/elife.37925
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple tumor suppressors regulate a HIF-dependent negative feedback loop via ISGF3 in human clear cell renal cancer

Abstract: Whereas VHL inactivation is a primary event in clear cell renal cell carcinoma (ccRCC), the precise mechanism(s) of how this interacts with the secondary mutations in tumor suppressor genes, including PBRM1, KDM5C/JARID1C, SETD2, and/or BAP1, remains unclear. Gene expression analyses reveal that VHL, PBRM1, or KDM5C share a common regulation of interferon response expression signature. Loss of HIF2α, PBRM1, or KDM5C in VHL-/-cells reduces the expression of interferon stimulated gene factor 3 (ISGF3), a transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 70 publications
5
19
0
Order By: Relevance
“…In a study of patients with clear cell RCC, patients with nuclei positive for IRF9 had a better prognosis than those with absent IRF9 expression. Similarly, to our findings in patients with lung cancer, the status of STAT2 did not influence survival in these patients [ 31 ]. In acute myeloid leukemia and prostate cancer, IRF9 acts as a tumor suppressor; in pancreatic diseases, it acts as an oncogene [ 29 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In a study of patients with clear cell RCC, patients with nuclei positive for IRF9 had a better prognosis than those with absent IRF9 expression. Similarly, to our findings in patients with lung cancer, the status of STAT2 did not influence survival in these patients [ 31 ]. In acute myeloid leukemia and prostate cancer, IRF9 acts as a tumor suppressor; in pancreatic diseases, it acts as an oncogene [ 29 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 88%
“…This result has been confirmed even in IFNα-resistant cells, such as in human glioblastoma multiforme [ 30 ]. In a renal cell adenocarcinoma study, IRF9 knockdown was shown to increase tumor formation in a xenograft model, whereas the overexpression of both IRF9 and STAT2 reduced tumor growth [ 31 ]. In lung adenocarcinoma (LUAD), IRF9 induced PD-L1 upregulation upon IFNβ stimulation, which indicates the presence of an immunosurveillance escape mechanism [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported in clear cell renal cell carcinoma, the loss of HIF2a, KDM5C or PBRM in VHL-/cells are able to downregulate the expression of ISGF3 [17]. Also, studies show that the loss of BAP1 or SETD2 reduces the expression level of ISGF3 which confirms its expression are interrelated to each other [17]. Correlating with ovarian cancer, the higher and lower expression of ISGF3 in initial and advanced stage of ovarian cancer may be also link with the related proteins like HIF2a, KDM5C, PBRM, BAP1 or SETD2.…”
Section: Discussionsupporting
confidence: 80%
“…The present investigation mainly focused on understanding ISGF3 expression pattern in different pathological stages of ovarian cancer. As previously reported in clear cell renal cell carcinoma, the loss of HIF2a, KDM5C or PBRM in VHL-/cells are able to downregulate the expression of ISGF3 [17]. Also, studies show that the loss of BAP1 or SETD2 reduces the expression level of ISGF3 which confirms its expression are interrelated to each other [17].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation